Strategi Komunikasi Radio Songgolangit FM dalam Menarik Minat Pendengar Studi Kasus Program Jumat Berkah - Feby Ayu Rusmayanti (Journal of Communication Studies, 2022)
Radio Songgolangit FM is one of the major radio stations in Ponorogo Regency with a large number of listeners. Feeling that all of this is not enough, Radio Songgolangit FM also holds a program that can maintain its existence and attract listeners, namely Friday blessing. Departing from this, it makes researchers interested and want to know how the implementation of the Friday blessing program is and what is the purpose of the Friday blessing program on Radio Songgolangit FM. For this reason, the writer is interested in conducting research on Songgolangit FM Radio in the form of a scientific paper with the title "Songgolangit FM Radio Communication Strategy in attracting listeners (Case Study of the Blessing Friday Program)". This research is a type of qualitative research with a case study approach. The data analysis process used uses data analysis techniques from Miles, Huberman, & Saldana (2014), namely the data undergoes 4 flow stages in the form of: data collection, condensation, data presentation, and drawing conclusions (Kriyantono, 2020). Data collection techniques in the form of in-depth interviews, observations, and document tracking activities. This research was conducted over a period of three months starting from November 2020 to January 2021. Located at Radio Songgolangit FM which is located at Jalan Halim Perdana Kusuma number 12, Tonatan Village, Ponorogo District, Ponorogo Regency, East Java Province. This study resulted in the finding that the Songgolangit FM Radio Blessing Friday program was carried out on Friday, precisely before the Friday prayer took place. The implementation of the Friday blessing program of Radio Songgolangit FM is carried out by employees with techniques, procedures, and distribution according to the direction of the company. The purpose of the Friday blessing program of Radio Songgolangit FM is to share and help our brothers and sisters in need, as well as to make the Friday blessing program to attract people's interest to listen to Radio Songgolangit FM. From the results of research that has been done at Radio Songgolangit FM, the authors provide suggestions for Radio Songgolangit FM to provide additional human resources, this aims to optimize employee performance in the implementation of the Friday blessing program.